Early Detection of Cardiac Damage by Two-Dimensional Speckle Tracking Echocardiography After Thoracic Radiation Therapy: Study Protocol for a Prospective Cohort Study - Zhu, Dan; Li, Tingcui; Zhuang, Hongqing; Cui, Ming (Frontiers in Cardiovascular Medicine, 2022)
Background: As one of the important treatment methods for cancer patients, radiotherapy may lead to incidental irradiation of the heart, resulting in radiotherapy-induced heart disease (RIHD) arising many years after radiotherapy. While, there are few studies on early subclinical cardiac damage, which may be essential for the protection of late RIHD. To detecte and predict RIHD and early subclinical cardiac damage induced by thoracic radiation therapy, based on two‑dimensional speckle tracking echocardiography (2D STE) combined with multiple circulating biomarkers and accurate heart dosimetry. Methods and analysis: This is a monocentric prospective cohort study in which 100 patients treated for malignant tumors and with cardiac radiation exposure will be included. According to whether they have chemotherapy history, participants will be divided into 2 groups and followed for 12 months after radiotherapy. Echocardiography, 2D STE, and blood samples will be underwent at 5-time points (baseline; after completion of RT; 2, 6, and 12 months after RT). Left ventricular ejection fraction (LVEF); global longitudinal, radial, and circumferential strain; diastolic function parameters; creatine kinase (CK); creatine kinase isoenzyme (CK-MB); cardiac troponin T (cTnT); N-terminal pro-B-type natriuretic peptide (NT-proBNP) and hypersensitive C-reactive protein (hs-CRP) will be measured at baseline and every follow-up time. The incidence of major adverse cardiovascular events will be recorded. Discussion: This study details the protocol and presents the primary limits and advantages of this single-center project. The inclusion of patients began in 2021, and the results are expected to be published in 2023. This study will be allowed to enhance knowledge on detection and prediction of early subclinical cardiac dysfunction induced by thoracic radiation therapy, based on two‑dimensional speckle tracking echocardiography (2D STE) combined with circulating biomarkers and accurate heart dosimetry. Furthermore, we will evaluate risk factors of subtle cardiac damage and identify high-risk groups for early heart damage.